The genus Gynacantha Rambur, 1842 in the South Pacific (Odonata: Anisoptera: Aeshnidae) - Theischinger, Gunther; Marinov, Milen; Bybee, Seth; Jensen, Colin; Theuerkauf, Jörn; Rashni, Bindiya (Zootaxa, 2020)
Available information on Gynacantha Rambur, 1842 species from the South Pacific is reviewed. Specimens were found to be sufficiently similar to G. rosenbergi Kaup in Brauer, 1867 to be placed in the same species group (G. rosenbergi group—established here) but also distinct enough to form a subgroup of its own (G. rosenbergi Pacific group). All species of the G. rosenbergi group are diagnosed, with three species, Gynacantha vitiana sp. n. (male and female) from Viti Levu, Fiji, G. koroana sp. n. (male) from Koro, Fiji and G. vanuatua sp. n. (male) from Malekula, Vanuatu being described as new to science. A key is presented for identification of the males.